SISTEM INFORMASI GEOGRAFIS (SIG) DATA AKADEMIK MAHASISWA S1 REGULER UNIVERSITAS GADJAH MADA - , MUHAMMAD FAHIMA HANIFA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Gadjah Mada University already had an undergraduate student academic information system presented in the form of charts and tables. The existing system cannot present data spatially. This study aims to improve the existing system by adding the ability to present data spatially combines with statistical graphs (chart). This geographical information system is developed using The GeoServer and OpenLayers tools. GeoServer is an open source application that can present geospatial data through a web map / feature service and can be accessed through web. While, OpenLayers is a javascript-based client application for displaying map data in web browsers. In addition, the developed system is also equipped with facilities for querying so the user can perform a query to get more various and specific spatial information.